Occurrence and Biological Cost of mcr-1-Carrying Plasmids Co-harbouring Beta-Lactamase Resistance Genes in Zoonotic Pathogens from Intensive Animal Production - Tiago Lima; Dina Loureiro; Ana Henriques; Fernando Ramos; Constança Pomba; Sara Domingues; Gabriela Jorge da Silva (MDPI AG, 2022)
Colistin is classified as a high-priority critical antimicrobial by the World Health Organization (WHO). A better understanding of the biological cost imposed by mcr-plasmids is paramount to comprehending their spread and may facilitate the decision about the ban of colistin in livestock. This study aimed to assess the prevalence of mcr and ESBL genes from 98 Escherichia coli and 142 Salmonella enterica isolates from food-producing animals and the impact of the mcr-1 acquisition on bacterial fitness. Only mcr-1 was identified by multiplex PCR (mcr-1 to mcr-10) in 15.3% of E. coli. Colistin MICs ranged between 8-32 mg/L. In four isolates, blaTEM-1, blaCTX-M-1, and blaCTX-M-15 co-existed with mcr-1. The IncH12, IncHI1, IncP, IncN, and IncI plasmids were transferred by conjugation to E. coli J53 at frequencies of 10−7 to 10−2 cells/recipient. Growth kinetics assays showed that transconjugants had a significantly lower growth rate than the recipient (p < 0.05), and transconjugants' average growth rate was higher in the absence than in the presence of colistin (1.66 versus 1.32 (p = 0.0003)). Serial transfer assay during 10 days demonstrated that plasmid retention ranged from complete loss to full retention. Overall, mcr-1-bearing plasmids impose a fitness cost, but the loss of plasmids is highly variable, suggesting that other factors beyond colistin pressure regulate the plasmid maintenance in a bacterial population, and colistin withdrawal will not completely lead to a decrease of mcr-1 levels.